Roll Cake Substitusi Tepung Beras Merah Isi Abon Lele Tinggi Kalsium Dan Zat Besi Pencegah Stunting Ibu Hamil: Roll Cake Substitusi Tepung Beras Merah Isi Abon Lele Tinggi Kalsium dan Besi Cegah Stunting - Michellia Gemma Kartika; Badra Lastariwati; Nani Ratnaningsih (Amerta Nutrition, 2022)
Background: Cases of stunted physical growth and development of infants and toddlers due to malnourished mothers and pregnant women, commonly referred to as stunting, are still common in Indonesia. Objectives: This study aims to determine the level of preference for a roll cake with brown rice flour substituted with shredded catfish and the nutritional content contained in a roll cake with substituted brown rice flour with shredded catfish for the prevention of stunting for pregnant women. Methods: This research uses R & D with a 4-D development model (Four D) consisting of 4 main stages, namely: Define, Design, Develop and Disseminate. Data collection was carried out by sensory tests (color, aroma, texture, taste, and overall) on products developed in 2020, with multiple T test data analysis. Results: Based on the preference test of 30 respondents, stated that there were significant differences in color and taste. Then aroma, texture, and overall stated there was no significant difference. Overall, people like the roll cake with brown rice flour filled with shredded catfish. Nutritional content of roll cake substitution of brown rice flour filled with shredded catfish: water 27.73%, ash 1.63%, protein 9.22%, fat 30.28%, carbohydrates 20.62%, energy 392.79%, calcium 34 ,45%, and 7.06% iron. Conclusions:The panelists favored the roll cake product with brown rice flour filled with shredded catfish, then the iron and calcium content increased significantly. So that it can be used as an additional snack for pregnant women to prevent stunting.